To determine whether the equation \( 3^{-5} \cdot (81^{\sqrt{4}})^{3} \cdot 3^{-4} = 3^{-6} \) is true or false, we will simplify each side.
-
Simplifying the left side:
- First, calculate \( \sqrt{4} \), which is \( 2 \), thus \( 81^{\sqrt{4}} = 81^{2} \).
- Since \( 81 = 3^{4} \), we can write: \[ 81^{2} = (3^{4})^{2} = 3^{8} \]
- Now plugging this back into the left side: \[ 3^{-5} \cdot (3^{8})^{3} \cdot 3^{-4} = 3^{-5} \cdot 3^{24} \cdot 3^{-4} \]
- Using the laws of exponents, we combine: \[ 3^{-5 + 24 - 4} = 3^{15} \]
-
Simplifying the right side:
- The right side is \( 3^{-6} \).
-
Comparing both sides:
- We have \( 3^{15} \) on the left and \( 3^{-6} \) on the right. Clearly, these two expressions are not equal.
Thus, the statement \( 3^{-5} \cdot (81^{\sqrt{4}})^{3} \cdot 3^{-4} = 3^{-6} \) is false.
Conclusion: The correct response is: False. The numerator simplifies to \( 3^{-2} \) and the fraction with numerator \( 3^{-2} \) and denominator \( 3^{-4} \) is not equal to \( 3^{-6} \).